Undesirable events in the use of high-alert medicine geriatric patients at RSUPN Dr. Cipto Mangunkusumo - Malihi, La; Supadmi, Woro; Trisna , Yulia; Purwanto , Barkah Djaka (Pharmaciana, 2025)
High-Alert Medications (HAM) are drugs that have a high risk of causing significant harm to patients if misused. It is estimated that one in ten geriatric patients experiences undesirable events during hospitalization related to medication use. Detect undesirable events due to the use of high-alert insulin and high-alert heparin drugs in geriatric patients at Rumah Sakit Umum Pusat Nasional (RSUPN) Dr Cipto Mangunkusumo using the trigger tool method based on positive predictive value (PPV) and determine the effect of using high-alert insulin and high alert heparin drugs on undesirable events. A retrospective cohort study will review secondary data from patient medical records (MR). The sample used was from 300 geriatric patients, 82 patients used insulin and 79 patients used heparin which met the inclusion criteria. Data were analyzed in the form of frequencies and percentages (%), calculation of PPV values, and the effect of using high-alert insulin and high-alert heparin on undesirable events using the Chi-Square test. There were 8 trigger-positive patients with undesirable events in the form of hypoglycemia from 82 insulin patients and 4 trigger-positive patients with undesirable events in the form of extended activated partial thromboplastin time (aPTT) values from 79 heparin patients. Based on the PPV value, both insulin (9.75%) and heparin (5.33%), the trigger tool has not been able to detect undesirable events when using high-alert insulin and high-alert heparin. Based on statistical tests, the p-value= 0.033 (p<0.05) for insulin and heparin p-value= 0.043 (p<0.05) meaning that there is an influence of the use of high-alert insulin and high-alert heparin on undesirable events when using both drugs. The trigger tool method cannot detect undesirable events when using high-alert insulin and high-alert heparin drugs based on laboratory triggers.